Optical and Photoacoustic Properties of Laser-Ablated Silver Nanoparticles in a Carbon Dots Solution - Amir Reza Sadrolhosseini; Ganesan Krishnan; Suhaidi Shafie; Suraya Abdul Rashid; Sulaiman Wadi Harun (Molecules, 2020)
This study used the carbon dots solution for the laser ablation technique to fabricate silver nanoparticles. The ablation time range was from 5 min to 20 min. Analytical methods, including Fourier transform infrared spectroscopy (FTIR), UV-visible spectroscopy, transmission electron microscopy, and Raman spectroscopy were used to categorize the prepared samples. The UV-visible and z-scan techniques provided optical parameters such as linear and nonlinear refractive indices in the range of 1.56759 to 1.81288 and 7.3769 × 10−10 cm2 W−1 to 9.5269 × 10−10 cm2 W−1 and the nonlinear susceptibility was measured in the range of 5.46 × 10−8 to 6.97 × 10−8 esu. The thermal effusivity of prepared samples, which were measured using the photoacoustic technique, were in the range of 0.0941 W s1/2 cm−2 K−1 to 0.8491 W s1/2 cm−2 K−1. The interaction of the prepared sample with fluoride was investigated using a Raman spectrometer. Consequently, the intensity of the Raman signal decreased with the increasing concentration of fluoride, and the detection limit is about 0.1 ppm.